KOSNTRUKSI VERBA SERIAL BAHASA RONGGA - Jeladu Kosmas (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2010)
Verb as filler of clausal predicate function of Rongga language, can appear in the form of sample verb, or serial verb. Although it consists of two verbs (V1 and V2), serial verbs of Rongga language perform as sample verbs in filling clausal predicate. Grammatical categorical patterns of performing serial verbs in Rongga language are (1) V1 intransitive-action + V2 intransitive static; (2) V1 intransitive-action + V2 transitive-action; (3) V1 transitive-action +V2 transitive-action+V2 intransitive process; (4) V1 transitive-action + V2 transitive-action. Semantically, serial verbs of Rongga language placed under one node in constituent, namely FV node.